Pengaruh struktur organisasi lembaga induk terhadap manajemen perpustakaan: Tinjauan dalam perspektif budaya organisasi - Fadhilatul Hamdani (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2014)
The organization structure of the main institutions greatly affect the management of the institution's own library. The research found that library y not fit into the organization structure of x explicitly, the library is only a complementary part to make the library be underestimated and was not an important part from the main organization. Another reason is not appointed someone to be head librarian who takes full responsibility and will have the authority to lead the library. That problem caused the library staff work without direction from a single command, so that the library management is not going well